CHD5 is required for neurogenesis and has a dual role in facilitating gene expression and polycomb gene repression - STREUBEL, GUNDULA; HOKAMP, KARSTEN (My University, 2013)
The chromatin remodeler CHD5 is expressed in neu- ral tissue and is frequently deleted in aggressive neuroblastoma.Verylittleisknownaboutthefunction of CHD5 in the nervous system or its mechanism of action. Here we report that depletion of Chd5 in the developingneocortex blocks neuronal differentiation and leads to an accumulation of undifferentiated progenitors. CHD5 binds a large cohort of genes and is required for facilitating the activation of neuronal genes. It also binds a cohort of Poly- comb targets and is required for the maintenance of H3K27me3 on these genes. Interestingly, the chro- modomainsofCHD5directlybindH3K27me3andare required for neuronal differentiation. In the absence of CHD5, a subgroup of Polycomb-repressed genes becomes aberrantly expressed. These findings pro- vide insights into the regulatory role of CHD5 during neurogenesis and suggest how inactivation of this candidate tumor suppressor might contribute to neuroblastoma.
PUBLISHED
Keywords: Polycomb-repressed genes; Polycomb-repressed genes